2017
DOI: 10.1653/024.100.0304
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Cinnamon Oil Improves Toxicity of Rotenone toSpodoptera litura(Lepidoptera: Noctuidae) Larvae

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The nonlinear isobologram demonstrated that the combination of cocaine and cannabinoid has synergistic effects on planarians (Raffa et al, 2007). When the ratio of rotenone to Cinnamomum cassia Presl oil is 1:35, the synergistic effect of rotenone on the third instar larvae is good for Spodoptera litura (Li et al, 2017; Wen et al, 2013). Carvacrol combined with thymol has a synergistic effect on Culex pipiens pallens (Diptera: Culicidae) and has the potential to be developed as a natural fumigant for mosquitoes (Ma et al, 2014).…”
Section: Application Of Isobologram Analysis To Evaluate Drug Interacmentioning
confidence: 99%
“…The nonlinear isobologram demonstrated that the combination of cocaine and cannabinoid has synergistic effects on planarians (Raffa et al, 2007). When the ratio of rotenone to Cinnamomum cassia Presl oil is 1:35, the synergistic effect of rotenone on the third instar larvae is good for Spodoptera litura (Li et al, 2017; Wen et al, 2013). Carvacrol combined with thymol has a synergistic effect on Culex pipiens pallens (Diptera: Culicidae) and has the potential to be developed as a natural fumigant for mosquitoes (Ma et al, 2014).…”
Section: Application Of Isobologram Analysis To Evaluate Drug Interacmentioning
confidence: 99%
“…seeds and Artemisia princeps Pamp leaves exhibited synergistic insecticidal and repellent activity against crop pests like Sitophilus oryzae L. (rice weevil) and B. rugimanus Bohem when combined at a concentration ratio of 1:1 [ 94 ]. A study showed that cinnamon oil was able to synergize the larvicidal activity of rotenone against Spodoptera litura (F.) at a mixture ratio of 1:35 and concentration of 506 mg/L within 72 h of exposure [ 95 ]. Essential oil compounds γ-terpinene and terpinen-4-ol ( Figure 3 ) isolated from the extracts of Majorana hortensis Moench were able to synergistically mediate insecticidal activity against Aphis fabae (Scopoli) and S. littoralis [ 96 ].…”
Section: Synergistic and Hybridized Insect Pest Management Products Of Botanical Essential Oilsmentioning
confidence: 99%
“…At the same time, a preliminary experiment showed its moderate fumigation activity (the fumigation mortality rate of 0.1 g of raw insecticide after 24 h of treatment was 66.67%, unpublished data). Several studies demonstrated the high toxicity of rotenone for pests, mites, and nematodes (Li et al, 2017; Means within a row, followed by the same lowercase letter(s), do not differ significantly at the 5% level according to Tukey"s multiple comparison test.…”
Section: Resultsmentioning
confidence: 99%